2018
DOI: 10.1002/hed.25354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between hemithyroidectomy alone and hemithyroidectomy with elective unilateral central neck dissection in patients with papillary thyroid microcarcinoma

Abstract: Background There have been arguments over the efficacy of elective unilateral central neck dissection (CND) in patients with papillary thyroid carcinoma (PTC) <1 cm who underwent hemithyroidectomy. This study was designed to investigate locoregional recurrence and postoperative complications related to elective unilateral CND for papillary thyroid microcarcinoma (PTMC). Methods Five hundred thirty‐seven patients who underwent hemithyroidectomy, with or without CND for PTMC, were included. We compared locoregio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
6
5
1
Order By: Relevance
“…In the present study, the incidence of multifocality (10·2 per cent) was comparable to previously reported rates ranging from 6·7 to 14·6 per cent, and this factor was identified as the sole predictor of recurrence. This result, together with the recurrence pattern, indicates that a degree of occult contralateral PTC led to frequent recurrence in the contralateral thyroid lobe.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, the incidence of multifocality (10·2 per cent) was comparable to previously reported rates ranging from 6·7 to 14·6 per cent, and this factor was identified as the sole predictor of recurrence. This result, together with the recurrence pattern, indicates that a degree of occult contralateral PTC led to frequent recurrence in the contralateral thyroid lobe.…”
Section: Discussionsupporting
confidence: 90%
“…The recurrence rate of 4·5 per cent in the present study was comparable to, or lower than, that in recent studies of PTC operated with hemithyroidectomy alone (3·1–13·0 per cent). Recurrence patterns in the present study were consistent with those of a recent study of 724 patients with PTC undergoing lobectomy only.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations